(untitled) (Germany, 2017)
This ready reference and handbook is unique in focusing on synthesis and the application of graphene and other carbon materials with an emphasis on chemistry aspects. It deals with top-down and bottom-up approaches, and presents the best synthetic methods.
Keywords: Hợp chất Carbon,Carbon compounds